Keynes : A Very Short Introduction - Skidelsky, Robert (Oxford Oxford University Press, 2010)
John Maynard Keynes was one of the most influential economists of the twentieth century. His ideas have had a central influence on many of areas of economics used today, both in theory and practice. In this Very Short Introduction Lord Robert Skidelsky looks at Keynes's life, his philosophy, his theories, and the legacy he left behind.
Include References and Index.
A Very Short Introduction.
Keywords: Keynesian economics -- Keynes, John Maynard, 1883-1946